2021
DOI: 10.1111/iju.14568
|View full text |Cite|
|
Sign up to set email alerts
|

Enzalutamide with androgen deprivation therapy in Japanese men with metastatic hormone‐sensitive prostate cancer: A subgroup analysis of the phase III ARCHES study

Abstract: To evaluate the efficacy and safety of enzalutamide plus androgen deprivation therapy in Japanese men with metastatic hormone-sensitive prostate cancer. Methods: A post-hoc analysis of the Japanese subgroup in the phase III, randomized, multinational ARCHES study (NCT02677896) was carried out. Patients with metastatic hormone-sensitive prostate cancer were randomized to receive enzalutamide or a placebo, plus androgen deprivation therapy, stratified by disease volume and prior docetaxel therapy. The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Forty-seven were removed as duplicates due to overlapping among databases. After screening the titles and abstracts and then the full texts, 27 publications 17 43 were shortlisted. No additional studies were identified from the bibliographic search.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-seven were removed as duplicates due to overlapping among databases. After screening the titles and abstracts and then the full texts, 27 publications 17 43 were shortlisted. No additional studies were identified from the bibliographic search.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies covered the whole spectrum of PC disease, including patients with nmCRPC ( n = 2), 17 , 18 mCSPC ( n = 4), 19 21 , 23 and mCRPC ( n = 19). Population included in all 15 real-world studies was patients with mCRPC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic benefit of the early intensive treatment was first introduced by the CHAARTED trial in 2014, followed by LATITUDE trial in 2017, which introduced the concept of “High Volume” and “High Risk”, respectively 1 . In 2019, the concept of upfront ARAT has been shifted to all metastatic prostate cancer patients based on the result of the ARCHES, 2 TITAN, and ENZAMET trials 1 …”
mentioning
confidence: 99%